2021
DOI: 10.1007/s00249-021-01560-2
|View full text |Cite
|
Sign up to set email alerts
|

KD determination from time-resolved experiments on live cells with LigandTracer and reconciliation with end-point flow cytometry measurements

Abstract: Design of next-generation therapeutics comes with new challenges and emulates technology and methods to meet them. Characterizing the binding of either natural ligands or therapeutic proteins to cell-surface receptors, for which relevant recombinant versions may not exist, represents one of these challenges. Here we report the characterization of the interaction of five different antibody therapeutics (Trastuzumab, Rituximab, Panitumumab, Pertuzumab, and Cetuximab) with their cognate target receptors using Lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Starting from our E1‐selective Ugi‐conjugated trastuzumab, we thus engaged it in a SPAAC step with a BCN‐fluorescein partner, effectively delivering the fluorescent conjugate T Ugi ‐Fluo (Figure 3). Gratifyingly, the latter showed rate constants of association and dissociation identical to those of the control FITC‐labeled trastuzumab T‐Fluo on HER2‐positive SKBR‐3 cells (i. e., k on =2.3×10 4 M −1 .s −1 , k off =1×10 −5 s −1 , K D =0.45 nM versus k on =2.0×10 4 M −1 .s −1 , k off =1.37×10 −5 s −1 , K D =0.69 nM, respectively), perfectly in line with previously reported values [38] . As further evidence of a maintained affinity, the ADC T Ugi ‐DM1 was produced by SPAAC, using a BCN‐DM1 strained alkyne (avDAR=1.0, 60–65 % conversion, 75 % yield due to partial precipitation of the ADC).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Starting from our E1‐selective Ugi‐conjugated trastuzumab, we thus engaged it in a SPAAC step with a BCN‐fluorescein partner, effectively delivering the fluorescent conjugate T Ugi ‐Fluo (Figure 3). Gratifyingly, the latter showed rate constants of association and dissociation identical to those of the control FITC‐labeled trastuzumab T‐Fluo on HER2‐positive SKBR‐3 cells (i. e., k on =2.3×10 4 M −1 .s −1 , k off =1×10 −5 s −1 , K D =0.45 nM versus k on =2.0×10 4 M −1 .s −1 , k off =1.37×10 −5 s −1 , K D =0.69 nM, respectively), perfectly in line with previously reported values [38] . As further evidence of a maintained affinity, the ADC T Ugi ‐DM1 was produced by SPAAC, using a BCN‐DM1 strained alkyne (avDAR=1.0, 60–65 % conversion, 75 % yield due to partial precipitation of the ADC).…”
Section: Resultssupporting
confidence: 91%
“…Gratifyingly, the latter showed rate constants of association and dissociation identical to those of the control FITClabeled trastuzumab T-Fluo on HER2-positive SKBR-3 cells (i. e., k on = 2.3×10 4 M À 1 .s À 1 , k off = 1×10 À 5 s À 1 , K D = 0.45 nM versus k on = 2.0×10 4 M À 1 .s À 1 , k off = 1.37×10 À 5 s À 1 , K D = 0.69 nM, respectively), perfectly in line with previously reported values. [38] As further evidence of a maintained affinity, the ADC T Ugi -DM1 was produced by SPAAC, using a BCN-DM1 strained alkyne (avDAR = 1.0, 60-65 % conversion, 75 % yield due to partial precipitation of the ADC). This ADC was tested in cell viability assays on both HER2-positive and HER2-negative cell lines (i. e., SKBR-3 and MDA-MB-231, respectively) against the marketed ADC Kadcyla, comprising the same linker-drug payload, but produced through stochastic lysine conjugation (avDAR = 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…They observed a slightly preferential binding for trastuzumab over pertuzumab in both antibody forms, namely, Fab or the complete IgG form [5]. Furthermore, Spiegelberg et al determined dissociation constants for HER2/trastuzumab and HER2/pertuzumab complexes using the ligand tracer technique on living cell lines [6]. Their study revealed ∆G bind values of −13.7 and −14.0 kcal•mol −1 for the trastuzumab and pertuzumab complexes, respectively, at 310 K.…”
Section: Introductionmentioning
confidence: 99%